1999
DOI: 10.1080/03075079912331380158
|View full text |Cite
|
Sign up to set email alerts
|

Academic research and student motivation

Abstract: This article reports an investigation into the relationship between student perceptions of lecturer research and motivation to study at university. A 71-item, Likert-type questionnaire was completed by 100 Oxford Brookes University final year undergraduates. The pattern of correlation between variables together with the results of a factor analysis, suggests that a relationship exists between type of student motivation and attitude to faculty research. It is proposed that Intrinsic Motivation, and a specific f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 16 publications
(27 reference statements)
1
44
0
1
Order By: Relevance
“…Shore, Pinker, and Bates 1990) of intrinsically motivated students (cf. Breen and Lindsay 1999). It seems that a less integrated way, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shore, Pinker, and Bates 1990) of intrinsically motivated students (cf. Breen and Lindsay 1999). It seems that a less integrated way, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Among the factors influencing how students perceive the link between research and teaching are the nature and level of the discipline, type and purpose of a course, the ability and motivation of the student, and the opportunity for personal interaction with teachers (Neumann 1994). Breen and Lindsay (1999) point towards student motivation: those who most appreciate research involvement are the intrinsically motivated students, while qualification-motivated students are indifferent to research activities, and the achievement-oriented students approach research negatively. We will discuss both the disadvantages and advantages perceived by the students as reported in the literature.…”
Section: Student Perspectivementioning
confidence: 99%
“…However, studies also showed that research involvement facilitates student-centred learning by increasing flexibility in determining course content (Jenson as cited in Breen & Lindsay, 1999). Other research suggested that the effects of research on students' learning also depend on the characteristics of the students.…”
Section: Research and Graduates' Competenciesmentioning
confidence: 99%
“…Other research suggested that the effects of research on students' learning also depend on the characteristics of the students. Breen and Lindsay (1999) asserted that students with intrinsic motivation and specific form of course competence are associated with positive attitudes towards research activity, while students with extrinsic motivation who are social and achievement oriented have negative attitudes towards research.…”
Section: Research and Graduates' Competenciesmentioning
confidence: 99%
“…This practice is not motivating to students in higher education. Students in higher education generally think that the use of research makes their learning more authentic, increases their credibility of information received and their motivation to learn through discovery as well as ensures that their knowledge is up to date (Breen & Lindsay, 1999;Jenkins, 2000;Lindsay, Breen, & Jenkins, 2002). Therefore, instructors in higher education should be encouraged to embark on research activities that are relevant to their teaching.…”
Section: Content and Currency Of Knowledgementioning
confidence: 99%